2021
DOI: 10.1177/11297298211005256
|View full text |Cite
|
Sign up to set email alerts
|

Distal snuffbox versus conventional radial artery access: An updated systematic review and meta-analysis

Abstract: Background: A comprehensive comparison of available data in terms of vascular complications between distal and conventional transradial access is still partial and a net benefit of such approach has not yet been clearly demonstrated. Objective: To provide an updated comparison of complications between distal and conventional transradial access used to perform coronary angiography and/or percutaneous coronary intervention performing a systematic review and meta-analysis. Data sources: Data were obtained searchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 25 publications
4
23
0
Order By: Relevance
“…According to our findings, Rigatelli et al [ 22 ] showed a systematic appraisal that comprised 8 eligible papers and 7693 patients (mean age 57.9 years for dTRA and 58.4 years for cTRA, respectively).…”
Section: Discussionmentioning
confidence: 54%
“…According to our findings, Rigatelli et al [ 22 ] showed a systematic appraisal that comprised 8 eligible papers and 7693 patients (mean age 57.9 years for dTRA and 58.4 years for cTRA, respectively).…”
Section: Discussionmentioning
confidence: 54%
“…e findings showed that the incidence of hematoma (1.20% vs. 1.24%, RR � 1.01; 95% CI: 0.49-2.07; p � 0.99), radial artery spasm (1.42% vs. 3.84%, RR � 0.91; 95% CI: 0.32-2.62; p � 0.86), and radial artery dissection (0.11% vs. 0.20%, RR � 0.63; 95% CI: 0.18-2.16; p � 0.46) were not significantly different between TRA and DRA, while the incidence of RAO was significantly lower in DRA than TRA (2.30% vs. 4.86%, RR � 0.51; 95% CI: 0.32-0.81, p � 0.004). Rigatelli et al [23] searched the literature published before December 22, 2020, in Medline, Scopus, and Web of Science and included 8 case-control studies with 7073 patients in the meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the current evidence is yet limited, and additional large-scale, multicenter RCTs are required to verify the findings. e meta-analyses by Hamandi et al [22] and Rigatelli et al [23] included non-RCTs. Despite the low grade of evidence, the findings still demonstrated that the incidence of RAO was significantly lower in DRA than TRA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations